Genomic characterization of Corynebacterium diphtheriae isolates from human origin in Brazil, 1974-2024 - Bokermann, Sérgio; Sacchi, Claudio Tavares; de Lemos, Ana Paula Silva; Takagi, Elizabeth Harummyy; Santos, Marlon Benedito Nascimento; Almendros, Rosemeire Capoani; Campos, Karoline Rodrigues; Carvalho, Eneas; Camargo, Carlos Henrique (Frontiers in Bacteriology, 2026)
IntroductionDiphtheria is a potentially fatal disease that still causes deaths mainly in unvaccinated children. Over the last decades, the incidence of this disease has reduced drastically in face to the increase in vaccination coverage. Diphtheria is mainly caused by toxigenic Corynebacterium diphtheriae, however, in more recent years, invasive infections due to nontoxigenic Corynebacterium diphtheriae have emerged. Given this epidemiological threat, the continued surveillance remains essential to guide prevention and control measures.MethodologyUsing whole genome sequencing, we characterized 299 Corynebacterium diphtheriae isolates, assessing their clinical origin, age distribution of patients, tox gene carriage, antimicrobial resistance markers, and phylogenetic relationships.ResultsThe tox gene was identified in 255 isolates (85.3%). Antimicrobial resistance genes aph(3’’)-Ib, aph(3’)-Ia, aph(6)Id, cmx, tet(33), tet(O), tet(W), and tet(Z) were detected in low (<10%) frequencies, but sul1 was found in 72 (24.1%) isolates. Phylogenetic analyses identified 11 main clades comprising 286 isolates, represented by 46 different sequence types (ST); the remaining 13 isolates were distributed in the other 12 ST. Twenty-one novel ST were described, comprising 51 isolates.DiscussionOur study represents the largest genomic survey of Corynebacterium diphtheriae in Latin America. These results enhance global understanding of diphtheria and reinforce the need for vigilance against reemergence in areas with suboptimal vaccination coverage.